Crisis management during anaesthesia: pneumothorax. Issue 3 (2nd June 2005) - Bacon, A K; Paix, A D; Williamson, J A; Webb, R K; Chapman, M J
Abstract : Background: Pneumothorax is a potentially dangerous condition which may arise unexpectedly during anaesthesia. The diagnosis is one of exclusion, as initial changes in vital signs (cardiorespiratory decompensation and difficulty with ventilation) are non-specific, and other causes of such changes are more common, whereas local signs may be difficult to elicit, especially without full access to the chest. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for pneumothorax, in the management of pneumothorax occurring in association with anaesthesia. Methods: Reports of pneumothorax were extracted and studied from the first 4000 incidents reported to the Australian Incident Monitoring Study (AIMS). The potential performance of the structured approach, using the combination of algorithims described above for each of the relevant incidents, was compared with the actual management as reported by the anaesthetists involved. Results: Pneumothorax was noted as a possible diagnosis in 65 reports; 24 cases had a confirmed pneumothorax, of which 17 were in association with general anaesthesia. It was considered that, correctly applied, the application of the algorithms would have led to earlier recognition of the problem and/or better management in 12% of cases. Conclusion: Any pneumothorax may become a dangerous tension pneumothorax with the application of positive pressure ventilation. Limited access to the chest during anaesthesia may compromise the diagnosis. Recognition of any preoperative predisposition to a pneumothorax (for example, iatrogenic or traumatic penetrating procedures around the base of the neck) and close communication with the surgeon are important. Aspiration diagnosis in suspected cases and correct insertion of a chest drain are essential for the safe conduct of anaesthesia and surgery.